Feasibility analysis of an electrogastrography sensor for digestion detection - Neves, Paulo Alexandre; Gonçalves, Norberto Jorge; Varanda, Pedro; Simões, João; Pires, Filipe; Garcia, Nuno M; Costa, Ricardo; Zdravevski, Eftim; Pires, Ivan Miguel (IEEE, 2023)
This paper presents a preliminary study on the use of an electrogastrography sensor for digestion detection and monitoring. The chosen architecture is based on the BITalino platform, with a three-lead sensor array and a data acquisition and communication board. Data is gathered through Bluetooth with a computer running OpenSignals software. Although currently a process to evaluate feasibility of other devices for dietary practice is not defined, this study focusses on analysis of detection, social acceptability, comfort, and battery life. The first results seem promising, with clear detection of stomach digestion movements. However, a more refined solution must be faced in order to improve on comfort and acceptability. Future work includes data processing and logging to help detect abnormal digestion patterns and the relation with nutrition quality.
Keywords: electrogastrography sensor , digestion detection , nutrition enhancement , system feasibility analysis